Caregiver burden and proxy-reported outcomes of people without natural speech: a cross-sectional survey study - Lena Ansmann; Anna Zinkevich; Sarah Anna Katharina Uthoff; Jens Boenisch; Stefanie Kalén Sachse; Tobias Bernasconi; Johanna Sophie Lubasch (BMJ Open)
Objective To examine interrelations between care-related burden on informal caregivers and their proxy assessments of outcomes in people without natural speech.Design A cross-sectional survey.Setting Data were collected in January 2019 from a postal survey of informal caregivers of people without natural speech who are insured by a large regional health insurance company in the German federal state of Lower Saxony.Participants n=714 informal caregivers of people without natural speech of all ages and with various underlying disabilities were identified and contacted via the health insurance company. Data from n=165 informal caregivers (26.4%) were obtained.Main outcome measures Caregiver burden (self-reported, Burden Scale for Family Caregivers), pragmatic communication skills of people without natural speech (proxy report, self-developed), health-related quality of life of people without natural speech (proxy report, DISABKIDS Chronic Generic Measure - DCGM-12) and functioning of people without natural speech (proxy report, WHO Disability Assessment Schedule 2.0).Results The analyses revealed significant associations between caregiver burden on the one hand and both proxy-reported health-related quality of life (b=−0.422; p≤0.001) and functioning (b=0.521; p≤0.001) on the other. Adding caregiver burden to the regression model leads to a substantial increase in explained variance in functioning (R² Model 1=0.349; R² Model 2=0.575) as well as in health-related quality of life (R² Model 1=0.292; R² Model 2=0.460).Conclusions Caregiver burden should be considered an important determinant when informal caregivers report outcomes on behalf of people without natural speech. Longitudinal studies are recommended to better understand the burdens experienced by caregivers when supporting people without natural speech.Trial registration number DRKS00013628.